Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar Siswa Kelas 3 MI Plus Walisongo Trenggalek - Setyaning Utami (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The purpose of this research is to determine the influence of the Think Pair Share Type Cooperative Learning Model on student learning outcomes and how much influence the Think Pair Share Type cooperative learning model has on the learning outcomes of Class 3 MI Plus Walisongo Trenggalek students. Quantitative research methods are methods where research data is in the form of numbers and analysis uses statistics. The type of research that will be carried out in this quantitative research has an experimental design. The design form of this experimental research is quasi experimental. The population of this study was all 38 grade 3 students at MI Plus Walisongo Trenggalek consisting of class 3A and class 3B. Data collection techniques use test methods and documentation methods. The data analysis technique consists of testing the requirements that need to be calculated/tested, namely normality and homogeneity. The technique used is the independent sample t-test technique, which is to determine the coefficient of difference between two data distributions. The use of the t-test technique is intended to see whether there are significant differences between the two samples from the control class and the experimental class. The results of the research show that based on the results of data analysis it shows that tcount is 4,684 > from ttable 1,688, which means that Ho is rejected and Ha is accepted. In conclusion, there is an influence of the Think Pair Share Type Cooperative Learning Model on the learning outcomes of Class 3 MI Plus Walisongo Trenggalek students. How much influence the Think Pair Share Type Cooperative Learning Model has on the learning outcomes of Class 3 MI Plus Walisongo Trenggalek students can be proven by the results of Sig. is 0.000. Because the Sig value. 0.000 < real level (= 0.05).